Literature Review : Kelengkapan Kode Topography dan Morphology pada Kasus Neoplasma - Dian Nur Muslimah; Deasy Rosmala Dewi; Laela Indawati; Lily Widjaja (SEHATMAS: Jurnal Ilmiah Kesehatan Masyarakat, 2023)
In the Medical Record for determining the cancer diagnosis code (Neoplasm), there are 2 codes, namely the topographic code and the morphology code. These two codes are very important because the topographic code is a code that shows the location of the tumor, while the morphology code is a code that shows the nature of the tumor. If the two codes are not included, it will not determine the level of malignancy of the tumor. The aim of the study was to identify the completeness of the topographic and morphological codes in neoplasm cases. Literature study conducted on 7 journals uploaded online in the span of 2011-2021. Search journals in this study using the keywords "completeness", "Topography and Morphology code" obtained through Google Scholar. The results of the literature review show that the completeness of topographic and morphological codes in neoplasm cases has not yet reached 100%. The highest completeness of topographic codes is 98% at Aisyiyah Hospital Malang in 2018. While the lowest percentage is 0% at MRCCC Siloam Semanggi Hospital in 2020 and Karanganyar District Hospital in 2011. The highest completeness of morphology codes is 82.4% at Santa Elisabeth Hospital Medan while The lowest percentage was 0% at MRCCC Siloam Semanggi Hospital in 2020, Bhayangkara Hospital, Aisyiyah Hospital, Dr Moewardi Hospital, and Karanganyar District Hospital. The incompleteness is due to 2 factors Man: Coder inaccuracy in coding, officers have not implemented coding procedures in neoplasm cases. Method: there is no SOP for coding neoplasms, there is no PA result sheet, and the doctor's writing is not clear and complete. In assigning codes to neoplasm cases, officers should code according to the SOP, so that the resulting code is complete and accurate.